The realization of a real-time distributed control systems using IEEE-1394 for humanoid robot - Cha, Y.-S.; Seo, E.-H.; Kim, D.; You, B.-J. (2010 IEEE International Conference on Robotics and Biomimetics, ROBIO 2010, 2010)
In this paper, we introduce the realization of a IEEE-1394 real-time distributed control system and a motor controller for a humanoid robot. The realization of the realtime distributed control system is executed in the humanoid robot MAHRU, developed by Korea Institute of Science and Technology. Also, we point out that bus reset problem of IEEE-1394 can result in a control break in a humanoid robot. By measuring the eye-diagram of the communication protocol, we check to deteriorate the communication environment of a robot. This results from interference of electromagnetic noises by high power motors and causes bus reset problem. We propose recovery remapping method as a solution of the problem. This way is to restore the IEEE-1394 communication environment by instantly bus remapping without the loss of control time. ？ 2010 IEEE.